Neddylation of Coro1a determines the fate of multivesicular bodies and biogenesis of extracellular vesicles. Issue 12 (8th October 2021) - Fei, Xuefeng; Li, Zhijie; Yang, Diya; Kong, Xianghui; Lu, Xinliang; Shen, Yingying; Li, Xu; Xie, Shaofang; Wang, Jiaoli; Zhao, Yongchao; Sun, Yi; Zhang, Jing; et al.
Abstract: Multivesicular bodies (MVBs) fuse with not only the plasma membranes to release extracellular vesicles (EVs) but also lysosomes for degradation. Rab7 participates in the lysosomal targeting of MVBs. However, the proteins on MVB that directly bind Rab7, causing MVB recruitment of Rab7 remain unidentified. Here, we show that Coro1a undergoes neddylation modification at K233 by TRIM4. Neddylated Coro1a is associated with the MVB membrane and facilitates MVB recruitment and activation of Rab7 by directly binding Rab7. Subsequently, MVBs are targeted to lysosomes for degradation in a Rab7‐dependent manner, leading to reduced EV secretion. Furthermore, a decrease in neddylated Coro1a enhances the production of tumour EVs, thereby promoting tumour progression, indicating that neddylated Coro1a is an ideal target for the regulation of EV biogenesis. Altogether, our data identify a novel substrate of neddylation and reveal an unknown mechanism for MVB recruitment of Rab7, thus providing new insight into the regulation of EV biogenesis.